COMPETITIVE ADVANTAGES OF INNOVATIVE MATERIALS WHILE THE CONSTRUCTION OF ROAD BASE STRENGTHENED LAYERS - E. A. Bedrin; E. A. Bedrina (Вестник СибАДИ)
Introduction. The introduction of innovative technologies and materials in road construction is difficult due to a number of constraints, the solution of which is an urgent task of the construction industry. The competitive advantages of innovative materials (polymer-mineral composition “Nicoflok”) relative to traditional ones are considered on the example of the soil strengthening technology. The results of the research show the inconsistency of the regulatory and legal framework of the road sector in terms of the innovative technologies (materials) application. Such results suggest quickly update, refining both the characteristics of materials and methods for assessing the usage effectiveness. Thus, it is possible to increase the reliability of decisions made on the repair and construction of roads, and, as a consequence, increase their service.Materials and methods. The research was carried out in the course of construction (repair) work on the pilot road sections, as well as after a year of their operation. The authors used the regulatory documents and standard test methods for determining the physic, mechanical and deformation characteristics of soils and materials reinforced by the Nicoflok. Taking into account the obtained characteristics of the materials, the authors calculated an equal strength pavement structure using a licensed software product. According to the developed design options, the estimated cost of pavement construction was also calculated.Results. The results of the research allow authors to conclude that the physic and mechanical characteristics of the reinforced material are improved. At the same time, the competitive ability for the additive usage also increases.Discussion and conclusions. The paper shows the inconsistency of the regulatory and legal framework in the road sector in terms of the application of innovative technologies (materials). Moreover, the authors suggest the need to quickly update, clarifying both the characteristics of materials and methods for evaluating the usage effectiveness.